The Effect of Enterprise Risk Management, Managerial Ownership, and Firm Size on Firm Value with Good Corporate Governance as a Moderating Variable in Banking Companies Listed on the Indonesia Stock Exchange - Nadia Maharani; Agrianti Komalasari; Reni Oktavia (Indonesian Journal Publisher, 2025)
This study aims to examine the effects of Enterprise Risk Management (ERM), managerial ownership, and firm size on firm value in banking companies, as well as to analyze the moderating role of Good Corporate Governance (GCG) as proxied by the audit committee. The research adopts a quantitative approach with a causal research design and utilizes panel data analysis. Secondary data were collected from the financial statements and annual reports of banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was determined using a purposive sampling technique, and the data were analyzed using panel data regression with the assistance of EViews 13 software. The findings reveal that ERM has a negative effect on firm value, managerial ownership does not have a significant effect on firm value, and firm size has a positive effect on firm value. Furthermore, GCG through the audit committee is found to moderate the relationship between ERM and firm value, indicating that effective governance strengthens the supervision of risk management practices. However, GCG does not moderate the relationship between managerial ownership and firm value, nor between firm size and firm value. These results suggest that the role of corporate governance in enhancing firm value in the banking sector is primarily associated with its effectiveness in overseeing risk management rather than ownership structure or firm scale.